An Injury Threshold Model for Two-Car Collisions - Krishnan, K. S.; Carnahan, James V.; Beckmann, Martin J. (Management Science, 1983)
A theoretical model which estimates the probability of injury to occupants of vehicles in two-car collisions is presented and evaluated. This model is based on considerations of principles from mechanics and observations from biomechanics. It is evaluated using two-car accident injury data. The validity of the model structure is supported because the differences between estimated numbers of injuries and observed numbers of injuries in two-car accidents were statistically insignificant. In contrast, the predictive accuracy was found to be unacceptable for three regression models from the published literature which were arbitrarily specified. The parameter estimates developed for the model provide a basis for tentatively evaluating the effect of vehicle size on the probability of injury to drivers of cars in two-car collisions.